2022
DOI: 10.14513/actatechjaur.00663
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Geometric Parameters in the Sustainability Development of Continuous Welded Rail

Abstract: Continuous Welded Rails (CWR) are a key infrastructure element in the safety and efficiency of rail transportation. Their correct exploitation (operational) requires surveying and diagnostic monitoring based not only on the results of rail displacement measurements, but also on the geometric parameters of the track in the horizontal (H) and vertical (V) planes. Many researchers have proposed different approaches for surveying and diagnostic monitoring of CWR. However, they do not refer to the determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It has been found that in curves with a radius of 600 m, the wear is 4 times less than in curves with a radius of 300 m [8]. In addition, more than 30 factors have an influence on the wear of the wheels of the rolling stock and the lateral wear of the rails on the curved track sections [9]. This article describes and analyses the following factors: or more [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that in curves with a radius of 600 m, the wear is 4 times less than in curves with a radius of 300 m [8]. In addition, more than 30 factors have an influence on the wear of the wheels of the rolling stock and the lateral wear of the rails on the curved track sections [9]. This article describes and analyses the following factors: or more [10].…”
Section: Methodsmentioning
confidence: 99%
“…This includes the processes involved in fitting rolling stock into curved sections of the track, considering both vertical and horizontal deviations, and the impact of these parameters on the life cycle of infrastructure elements. The latter is directly dependent on the geometric parameters of the rail track [9]. The publication also covers the repair of rail defects with a focus on determining hardness parameters in the contact zone [10].…”
Section: Introductionmentioning
confidence: 99%
“…The paper looked at the efficiency of remedial maintenance and the rates of track deterioration on a regional railroad. Also, to identify critical elements for sustainable development, [5] investigated actual measurement data of six geometric parameters of continuously welded rail (CWR). According to their results, vertical irregularities are important in the vertical plane (V-plane), but the track gauge gradient and horizontal irregularities are crucial in the horizontal plane (H-plane).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the main problems regarding the theory of elastic stability for different types of elements (columns, beams, frames, rings, curved bars, arches, thin plates, and thin shells), were synthesized by S. P. Timoshenko and J. M. Gere in a reference book in the scientific literature [ 2 ]. The loss in stability of structural elements takes place under the action of compressive loads [ 3 , 4 ] or bending (lateral buckling of beams) [ 2 , 5 , 6 ]. The optimized designs of such elements involve modifying geometry in order to increase the critical buckling force and ensure a low weight.…”
Section: Introductionmentioning
confidence: 99%